Th17 cytokines and Vaccine Induced Immunity - Lin, Yinyao (2010)
T helper type 17 (Th17) cells are a distinct lineage of T cells that produce the effector molecules IL-17, IL-17F, IL-21 and IL-22. Although the role of Th17 cells in primary immune responses against infections is well documented, there is growing evidence that the Th17 lineage maybe critical for vaccine-induced memory immune responses against infectious diseases. Here we summarize recent progress in our understanding of the role of IL-17 in vaccine-induced immunity.